2011
DOI: 10.2131/jts.36.121
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced elimination of tissue methylmercury in Parachlorella beijerinckii-fed mice

Abstract: Chlorella (Parachlorella beijerinckii) on the excretion and tissue accumulation of methylmercury (MeHg), we orally administered 5 mg/kg of MeHg chloride (4 mg Hg/kg) to female C57BL/6N mice (aged 10 weeks). The mice were housed in metabolism cages to collect urine and feces for 3 weeks with diets containing 0%, 5%, or 10% P. beijerinckii powder (BP) in -increases in the cumulative Hg eliminations into urine (5% BP) and feces (5% and 10% BP) were found in the BP groups. Twenty-one days after administration, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…The neonate and mother blood levels in the CP diet group were lower by 13.6% and 15.0%, respectively, than the basal diet group. In the case of a single injection of MeHg to female mice of the same strain, CP-induced reduction of the blood Hg became significant for the first time as late as 7 days after injection (Uchikawa et al, 2011). The sustained MeHg exposure for several weeks in this study might be more suitable than a single injection to detect the effects of CP to reduce blood Hg levels.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The neonate and mother blood levels in the CP diet group were lower by 13.6% and 15.0%, respectively, than the basal diet group. In the case of a single injection of MeHg to female mice of the same strain, CP-induced reduction of the blood Hg became significant for the first time as late as 7 days after injection (Uchikawa et al, 2011). The sustained MeHg exposure for several weeks in this study might be more suitable than a single injection to detect the effects of CP to reduce blood Hg levels.…”
Section: Resultsmentioning
confidence: 78%
“…We have recently reported that Hg excretions into feces and urine in MeHg-treated female mice increase with co-administration of CP (Uchikawa et al, 2010) or feeding a CP diet (Uchikawa et al, 2011). Although we did not collect urine and feces using a metabolism cage in the Tissue Hg level (μg/g) was divided by blood Hg levels (μg/ml) in each mouse, and the mean ± S.D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we found that Chlorella increased mercury excretion and lowered tissue mercury levels in MeHgtreated mice (Uchikawa et al, 2010(Uchikawa et al, , 2011. Fecal excretion constitutes a major route for the elimination of MeHg, about 90% of the total elimination, in most animal species including humans (Norseth and Clarkson, 1970;Miettinen et al, 1971;Komsta-Szumska et al, 1983;WHO, 1990).…”
Section: Results and Discussonmentioning
confidence: 90%
“…Thus, the discovery of a food material that could help detoxify the body from MeHg would be considered to beneficial to human health. We previously reported that Chlorella promoted the excretion of MeHg in both feces and urine, such that long-term administration of Chlorella enhances the elimination of tissue methylmercury in mice (Uchikawa et al, 2010(Uchikawa et al, , 2011. Here we studied the effect of 3-month Chlorella supplementation on mercury concentrations of blood and hair in healthy subjects.…”
Section: Introductionmentioning
confidence: 97%